MOTIVASI METRAE DAN NYALENE PADA MASA PERTUNANGAN DI KALANGAN MASYARAKAT MADURA PERSPEKTIF ‘URF - Jalil, Abdul Jalil; Kholisatun (Indonesian Association of Islamic Family Law Lecturers, 2019)
Madura region with diverse cultural backgrounds which become its specialty always ignores the attention of researchers to uncover, as it has become unique on most of Madura Island, especially Pamekasan at the time of engagement, a man who has been engaged in carrying out the tradition of carrying out traditions in the form of metrae and nyalene. Metrae and nyalene are usually done by the community in the last 10 months of Ramadan, together with the obligation to issue zakat fitrah for Muslims and end before the Eid Al-Fitr prayers. The submission of pertra and salenan is usually done by the parents of the male fiance, but there is a small portion of the men who are engaged to visit the residence of the female fiance with petra and salenan. Petra and salenan in the form of rice or money worth the petra and the salenan, sometimes in the form of a piece of cloth, a set of clothes or enough money to buy clothes. The tradition of metrae and nyalene is carried out, because it is driven by the desire to help each other and help reduce the burden of the female fiancee, to strengthen the bond of friendship between the two, the love that is being knitted can be bound until the time to hold a marriage contract. By submitting petra and salenan mean to imply that engagement prepared forwarded. Metrae and nyalene both form, scope and motivation of the implementer are included in the 'urf saheeh , namely, customs that apply in the midst of society and do not conflict with the Qur'an and Hadith texts, do not violate religious principles, do not contradict with reason and human mind, does not eliminate prosperity and does not bring harm even, to carry out and preserve this tradition, including carrying out religious principles in the form of help to help